0817 Conquering Two Sleep Birds with One Iron stone: The Case of Resolved Restless Sleep Disorder and Parasomnia with Iron Therapy. (25th May 2022) - Richens, Zachary; Ibrahim, Sally
Abstract: Introduction: Restless Sleep Disorder (RSD) is characterized by frequent nocturnal movements of large muscle groups or a complaint of restless sleep by observers with associated daytime dysfunction.1 RSD, like other movement disorders of sleep, is associated with low iron stores.2 Children with RSD have increased NREM sleep instability and a propensity for parasomnia.2 No reports to date have demonstrated the use of iron therapy for parasomnia in patients with RSD. Furthermore, studies are limited in very young children with this disorder as they currently fall outside proposed diagnostic criteria.1 Report of Cases: A 2 year-old male presented to the sleep clinic with parental complaints of nightly sleep initiation and maintenance difficulty, mild snoring, restless sleep, episodes of sleepwalking and night terrors multiple times per week. Symptoms worsened over 6 months and were associated with daytime irritability and behavioral problems. Sleep quality measures assessed progress between visits: the PROMIS Sleep Disturbance (PROMIS SD) and Sleep Related Impairment (PROMIS SRI). Serum ferritin was initially 20ug/L. Polysmnogram demonstrated no significant sleep related breathing disorder, a large muscle group movement index of 14, periodic limb movement index of 3. Initial treatment included oral iron therapy, scheduled awakenings, and hypnotic dose melatonin. The sleep psychologist addressed limit setting and negative sleep associations with improved insomnia symptoms but parasomnia and restless sleep continued. The parent noted reduction in both movements and parasomnia frequency after one month of iron therapy. After a 3 month period on treatment, the parent reported complete cessation of the parasomnia, drastic reduction in restlessness, and near resolution of insomnia. Sleep quality measure PROMIS SD improved by 11, demonstrating reduced sleep disturbance. PROMIS SRI did not change. Ferritin level increased to 47ug/L. Conclusion: RSD in a very young child with NREM parasomnia responded to oral iron therapy improving overall sleep quality. This case demonstrates the relationship between relative iron deficiency, RSD and associated parasomnia. Support (If Any): 1. DelRosso LM, Ferri R, Allen RP, et al. Consensus diagnostic criteria for a newly defined pediatric sleep disorder: restless sleep disorder(RSD).SleepMed.2020;75:335-340. 2. Leung W, Singh I, McWilliams S, Stockler S, Ipsiroglu OS. Iron deficiency and sleep - A scoping review. SleepMedRev.2020;51:101274